Female breast cancer in different age groups: clincopathological features and treatment strategies - Nuzhat, Ayesha; Abouzaid, Lamyaa Z. (International Journal Of Community Medicine And Public Health, 2017)
Background: The proportion of breast cancer cases have been alarmingly increasing. In order to investigate the clinical and pathological features of breast cancer arising in all age groups and to provide evidence for therapy based on these features, we intended to conduct this study among three age groups, young (age ≤40), middle aged (>40-50) and elderly patients (>50). Methods: This cross-sectional study obtained data from the cancer center registry at King Fahad Medical City and included all women diagnosed as breast cancer between 1st January 2011 till 31st December 2012 and followed until December 2015 (n=155). Results: 25.2% patients were ≤40 years of age, 38.7% were >40-50 years and 36.1% were >50 years. The upper outer quadrant of the breast was most frequently area involved in all the three age groups. Majority of the cases were Invasive Ductal Carcinoma (IDC). 51.3% cases were of grade III in patients ≤40 years, 43.3% cases in the middle age group (>40-50 years) were of grade II and 44.6% patients were of grade III in the elderly group. More T3 tumours were noticed in the younger group and more T2 in the middle age group and greater lymph node involvement N2 in the age group >50 years. The mean survival time for patients’ ≤40 was 37.6 months, 39.3 months for cases >40-50 years and 38.3 for patients >50 years old at the end of three years of follow up. At our cancer centre and among all the groups, majority of patients were treated with a combination of surgery, chemotherapy and radiation Conclusions: This study identifies cliniopathological features of breast cancer in all age groups in a tertiary care center, Saudi Arabia. Distant metastasis was more prevalent among younger age group and the middle aged women had the best mean survival time after three years.